Implementasi Model Problem Based Instruction (PBI) dalam Upaya Peningkatan Hasil Belajar Siswa - Rahmatul Husna Arsyah; Nizwardi Jalinus; Rijal Abdullah; Astri Indah Juwita (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2022)
The main problem in this study is how to improve student learning outcomes by using the Problem Based Instruction (PBI) learning model. The purpose of this study is to improve student learning outcomes on network infrastructure administration material. The results of the initial condition research using interviews, observation and item analysis, class XI students of SMK N 2 Padang City as research subjects, have an average learning achievement score that is below the minimum completeness criteria (KKM). This research is a Classroom Action Research (CAR) with a procedural model developed by Kemmis and Mc. Taggart is a spiral research model that is commonly used and consists of two cycles. Each cycle consists of four stages, namely: 1) the planning stage 2) the acting stage, 3) the observing stage and 4) the reflection stage. The number of research subjects consisting of 22 students. From the research results, it was obtained data that the PBI model can improve learning outcomes in network infrastructure administration (AIJ). This is indicated by the value of the results given in the initial conditions, from 22 students, the results obtained were 55% of students who did not complete. After the action was taken in cycle 1, student learning outcomes increased to 50% of students who completed, and continued to increase in the second cycle, with a completeness percentage of 81%.